Modelling and Control of a Multi-Cell Converter Based on Input-Parallel Output-Parallel Bridge-Cells with Discontinuous Interleaved Modulation - Rojas-Lobos, F; Diaz-Diaz, M; Verdugo-Naranjo, D (Institute of Electrical and Electronics Engineers Inc., 2021)
Multi-cell converters increase their current rating by adding more cells in parallel, if also the cells are interleaved the output THDi and input ripple get lower reducing the filter requirements. However interleaving causes circulating currents that need to be mitigated. This work proposes a model and control strategy that decouple the circulating currents from the output current under discontinuous modulation of a multi-cell converter based on Input-Parallel Output-Parallel (IPOP) bridge-cell. The discontinuous modulation eliminates the circulating current between one leg of the bridge cells. The proposed model and control are verified by simulations in Plecs. © 2021 IEEE.